Analisis Pengembangan Berpikir Kreatif Siswa pada Kegiatan Wirausaha di MI Amanah Kecamatan Turen - Denna Delawanti Chrisyarani; Prihatin Sulistyowati; Emi Firdayanti (Jurnal Bidang Pendidikan Dasar, 2021)
The purpose of this research to describe implementation, efforts and the impact of entrepreneur's activities on the development of creative thinking students in MI Safeah Turen District. This qualitative study uses the instrument of research sheet, questionnaire and documentation. Subject this study is the teacher, students class III and IV in MI Amanah Turen. Data analysis techniques in this study are a model of interaction analysis of data collection, reduction data, data presentation and conclusion withdrawals. The results show that the development of creative thinking of students through entrepreneur's activities is seen when students have a sense of confidence and to be brave in the delivery of ideas and promotion, the new product creations, forms, packaging with delicious, healthy, affordable prices and benign services. Entrepreneurial activities have a positive impact in the form of developing students' creative thinking which includes 4 aspects, namely fluency, flexibility, originality and detail.